2019
DOI: 10.3961/jpmph.19.146
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Associations Between Serum Hemoglobin Levels and the Risk of Cause-specific Death in Korea Using the National Health Insurance Service-National Health Screening Cohort (NHIS HEALS)

Abstract: ObjectivesThe purpose of this study was to determine the associations between blood hemoglobin (Hgb) levels and the risk of death by specific causes.MethodsUsing the National Health Insurance Services-National Health Screening Cohort (n=487 643), we classified serum Hgb levels into 6 sex-specific groups. Cox regression analysis was used to analyze the associations between Hgb levels and the risk of cause-specific death.ResultsHgb levels in male population showed a U-shaped, J-shaped, or inverse J-shaped associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These are not solely risk factors for cardiovascular diseases, but also increase the risk of cancer ( 19 ). Our study applied single-factor and multivariate logistic analyses and found that CAD, cancer and combined CAD and cancer shared a common risk factor, FIB levels ( 20 , 21 ), and a common protective factor, HGB levels ( 22 , 23 ). The phenomenon that CAD and cancer possess various similarities and interactions suggests a shared biology for the two diseases.…”
Section: Discussionmentioning
confidence: 97%
“…These are not solely risk factors for cardiovascular diseases, but also increase the risk of cancer ( 19 ). Our study applied single-factor and multivariate logistic analyses and found that CAD, cancer and combined CAD and cancer shared a common risk factor, FIB levels ( 20 , 21 ), and a common protective factor, HGB levels ( 22 , 23 ). The phenomenon that CAD and cancer possess various similarities and interactions suggests a shared biology for the two diseases.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, dysfunctional hemoglobin may influence the oxygen transporting capacity of erythrocytes which subsequently lead to hypoxia and releasing free radicals at the inflammatory sites (31). Remarkably , the difference in hemoglobin level between the two genders is regarded to be caused by a direct stimulatory factor of androgen in males in bone marrow coupled with erythropoietin production in the kidney , and the inhibitory effect estrogen on the bone marrow in women, this action of hormones promotes hemoglobin level in males compared with females (32). Recently , it has been reported that anemia is a major public health issue that affects women (33).…”
Section: Discussionmentioning
confidence: 99%
“…The combined effect of high combined BP and anemia played a significant role in increasing the mortality of both CVD and stroke. Based on the fact that the presence of anemia is an independent risk factor for CVD events [ 32 34 ], anemic status accompanied by high BP might exacerbate the ischemic condition, resulting in higher CVD morbidity and mortality. Contrary to our expectation, high combined BP was associated with increased total CVD and stroke-specific mortality in the younger age group, as well as the risk of earlier death.…”
Section: Discussionmentioning
confidence: 99%